Analisis Pedigree dan Fenotip Pasangan Kembar: Studi Kasus Pada Keluarga Kembar di Kecamatan Laweyan, Surakarta - Machwiyah, Yuyun; Satuti Nur Handayani, Niken (Jurusan Biologi UIN Alauddin Makassar, 2013)
The twin pregnancy is a kind of pregnancy with two or more fetuses. Basically, the twins can be grouped of two, they are fraternal twins (dizygotic) and identical twins (monozygotic). Fraternal twin is a kind of twins that comes from two ova, which each of them will be fertilized by the sperm. While, identical twin comes from an ovum, which fertilized by a sperm. This research is conducted in order to observe the inheritance pattern from the pedigree chart, and to observe similarity and dissimilarity phenotype between twin couple on families observed. Methods used for this research are data collection to construct pedigree, phenotype analysis to compare the similarity and dissimilarity phenotype between the twins that are observed, paraffin method to observe the form of hair from cross section and agglutination reaction to observe the blood group from the twins. Based on pedigree chart of twins in Laweyan, Surakarta, it seems that the identical twins is passedfrom generation to generation, and on the family observed the inheritance pattern of identical twins birth process is come from the women of identical twins. The lobe of ear from each twins there is a twin couple showing the different lobe. There is any similarity and dissimilarity relate to form of hair cross section from each couple. The blood group of each couple are showing the same result.Keywords: identical twins, inheritance pattern, pedigree chart